2015
DOI: 10.48550/arxiv.1505.00974
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Fibered Multiderivators and (co)homological descent

Abstract: The theory of derivators enhances and simplifies the theory of triangulated categories. In this article a notion of fibered (multi-)derivator is developed, which similarly enhances fibrations of (monoidal) triangulated categories. We present a theory of cohomological as well as homological descent in this language. The main motivation is a descent theory for Grothendieck's six operations. NotationWe denote by CAT the 2-"category" 1 of categories, by (S)MCAT the 2-"category" of (symmetric) multicategories, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
2
2

Relationship

4
0

Authors

Journals

citations
Cited by 4 publications
(25 citation statements)
references
References 10 publications
0
25
0
Order By: Relevance
“…In [11] we showed that all isomorphisms of 0.1 follow from this definition. We explain in Section 8 that enlarging the domain of 2-morphisms to all morphisms, or to a class of "proper", or "etale" morphisms, respectively, one can easily encode all sorts of more strict sixfunctor-formalisms, where either f !…”
Section: 1mentioning
confidence: 81%
See 3 more Smart Citations
“…In [11] we showed that all isomorphisms of 0.1 follow from this definition. We explain in Section 8 that enlarging the domain of 2-morphisms to all morphisms, or to a class of "proper", or "etale" morphisms, respectively, one can easily encode all sorts of more strict sixfunctor-formalisms, where either f !…”
Section: 1mentioning
confidence: 81%
“…For a detailed introduction to derivators and fibered multiderivators we refer to [11]. Stable derivators, among other things, simplify, enhance and conceptually explain triangulated categories.…”
Section: Fibered Multiderivatorsmentioning
confidence: 99%
See 2 more Smart Citations
“…a small category) and a functor S ∶ I → S form a 2-category Dia op (S), called the category of diagrams in S (cf. also [5]). A morphism of S-diagrams (α, µ)…”
Section: Introductionmentioning
confidence: 87%